Projected Climate‐Driven Changes of Water Table Depth in the World's Major Groundwater Basins. Issue 3 (22nd March 2023) - Costantini, Maya; Colin, Jeanne; Decharme, Bertrand
Abstract: As groundwater found in aquifers is the main reservoir of freshwater for human activity, knowledge of the future response of groundwater to climate change is key for improving water management adaptation plans. We analyze the climate‐driven evolution of future levels of unconfined aquifers in the 218 world's major groundwater basins in global climate simulations following the latest Intergovernmental Panel on Climate Change scenarios, run with models able to capture feedbacks among climate, land use and groundwater. We find a rising of groundwater levels on global average, which is consistent with the projected global intensification of precipitation. This signal presents large regional disparities which mostly match the patterns of precipitation changes. As the climate models we used do not simulate human groundwater withdrawals (irrigation as well as domestic and industrial uses) which represent the other main driver of groundwater levels evolution, we also use Food and Agriculture Organization maps of present‐day irrigated areas and projections of population in 2100 to identify regions where groundwater withdrawals could exacerbate the projected depletion, or even reverse a projected rise into a depletion. Depending on the scenario, we then find a rise (respectively a depletion) of groundwater levels in 2100 over 33%[28–39]% to 42%[41–45]% (respectively 26%[25–32]% to 37%[36–40]%) of the area covered by the 218 world's major groundwater basins. And we estimate that 31%[29–36]% to 43%[42–44]% of the world's population could be affected by these groundwater changes, facing either water scarcity issues (for 29%[27–33]% to 40%[39–40]% of the population), or increased risks of flooding (for 1.7%[1.5–2.2]% to 2.2%[2.2–2.4]% of the population). Key Points: The impact of climate change on water table depth (WTD) in the world's major groundwater basins is assessed using the sixth phase of the Coupled Model Intercomparison Project (CMIP6) global simulations Projections run with four shared socioeconomic pathways scenarios show a global rising of groundwater by 2100, with the occurrence of a depletion in numerous regions In 2100, 31%–43% of the world's population could face water scarcity issues or flood risks worsened by these WTD changes